Normative values for lung, bronchial sizes, and bronchus-artery ratios in chest CT scans: from infancy into young adulthood - Lv, Qianting; Chen, Yuxin; Caudri, Daan; Andrinopoulou, Eleni-Rosalina; Kuo, Wieying; Charbonnier, Jean-Paul; Fleck, Robert J.; Soler, Luis Riera; Paoletti, Matteo; Vermeulen, Francois; Morana, Giovanni; Lee, Edward Y.; et al. (European radiology, 2025)
Objective To estimate the developmental trends of quantitative parameters obtained from chest computed tomography (CT) and to provide normative values on dimensions of bronchi and arteries, as well as bronchus-artery (BA) ratios from preschool age to young adulthood. Materials and methods Two independent radiologists screened a dataset of 1160 chest CT scans, initially reported as normal, from participants aged 0 to 24 years. Using an automated deep learning-based algorithm, we computed the following bronchus and artery parameters: bronchial outer diameter (B out ), bronchial inner diameter (B in ), adjacent pulmonary artery diameter (A), bronchial wall thickness (B wt ), bronchial wall area (B WA ), and bronchial outer area (B OA ). From these parameters, we computed the following ratios: B out /A, B in /A, B wt /A, B wt /B out , and B WA /B OA . Furthermore, mean lung density, total lung volume, and the square root of wall area of bronchi with a 10-mm lumen perimeter (Pi10) were obtained. The effects on CT parameters of age, sex, and iodine contrast were investigated using mixed-effects or regression model analyses. Results 375 normal inspiratory chest CT scans (females / males = 156 / 219; mean age [SD] 12.7 [5.0] years) met the inclusion criteria. B out and B in progressively increased with age (all p < 0.05), but B wt , B out /A, B in /A, B wt /A, B wt /B out , or B WA /B OA did not. Total lung volume and mean lung density continuously increased with age (both p < 0.001), while Pi10 did not exhibit such a trend. B out , total lung volume, and mean lung density were the only parameters that differed between males and females, all higher in males than females (all p < 0.03). The presence of iodinated contrast led to greater values for B wt , B wt /B out , and B WA /B OA , but lower values for B in , B out /A, B in /A, and B wt /A (all p < 0.01). Conclusion Quantitative CT parameters of both lung parenchyma and bronchi exhibit growth-related changes, but from 6 to 24 years ratios between bronchus and artery dimensions remain constant. Contrast-enhanced CT scans affect the assessment of lung parenchyma and bronchial size. We propose age and technique-dependent normative values for bronchial dimensions and wall thickness. Key Points Question What are the developmental trends of quantitative lung CT parameters in patients from childhood into young adulthood? Findings The ratio between bronchus and pulmonary artery dimensions demonstrates consistent values across age groups, indicating synchronized growth between bronchi and paired pulmonary arteries. Clinical relevance Our findings highlight the importance of standardized CT protocol and volume acquisition, and emphasize the need for ongoing collection of normal chest CT scans to refine the proposed reference values.